2021
DOI: 10.1111/inr.12636
|View full text |Cite
|
Sign up to set email alerts
|

Nursing management at a Chinese fever clinic during the COVID‐19 pandemic

Abstract: Background The rampant spread of the novel coronavirus disease (COVID‐19) has assumed pandemic proportions across the world. Attempts to contain its spread have entailed varying early screening and triage strategies implemented in different countries and regions. Aim To share the experience of scientific and standardized management of fever clinics in China, which provide the first effective checkpoint for the prevention and control of COVID‐19. Introduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 7 publications
2
14
0
5
Order By: Relevance
“…The fever clinic plays an important role in the early detection, isolation and referral of patients presenting with fevers of unknown origin [ 24 ]. As a dedicated space for the diagnosis and treatment of suspected COVID-19 patients, the fever clinic is equipped with a mobile digital X-ray system, lead screen, protective lead clothing, water bath and medical-grade air-purifier in addition to the usual equipment set in the general clinic.…”
Section: Resultsmentioning
confidence: 99%
“…The fever clinic plays an important role in the early detection, isolation and referral of patients presenting with fevers of unknown origin [ 24 ]. As a dedicated space for the diagnosis and treatment of suspected COVID-19 patients, the fever clinic is equipped with a mobile digital X-ray system, lead screen, protective lead clothing, water bath and medical-grade air-purifier in addition to the usual equipment set in the general clinic.…”
Section: Resultsmentioning
confidence: 99%
“…In-person training, as an essential conventional training method, requires substantial financial and time resources, which results in participants feeling nervous and increases the risk of infection. 25 Therefore, alternative methods for spatial training in the clinic are needed, especially in crisis periods. Our study aimed to explore the feasibility and experience of transitioning in-person training to VR training, and it showed that implementing VR training is acceptable among nurses in special periods.…”
Section: Discussionmentioning
confidence: 99%
“…If it is impossible to deal with them, it should be carefully explained to patients and their families to make them feel at ease. As the first‐line of defence of hospital departments, fever clinics play a vital role during the outbreak of the COVID‐19 epidemic in China (Wang et al, 2021 ). Managers should also pay attention to the construction of fever clinics during regular epidemic prevention and control.…”
Section: Discussionmentioning
confidence: 99%